Political Identity as a Security Factor of Ukrainian Statehood - Prymush, Mykola; Lavrynenko, Hanna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
In the article, the authors analyze the formation of the political identity of citizens of Ukraine as a security factor of Ukrainian statehood. It is noted that, in addition to political identity, there are many other identities, that are presented in the form of a matrix, the components of which continuously interact with, complement and influence each other. In terms of methodology, the process of forming political identity is considered from the standpoint of symbolic interactionism, where the emphasis is placed on political interaction. In addition, in order to objectively assess the effectiveness of the formation of political identity and potential negative consequences in the form of a crisis of statehood, the mechanism for transforming a situational identity into a basic political identity is considered from the standpoint of post-structuralism. The study identifies and formulates criteria for constructing this basic type of political identity, the prerequisites for their formation and correlation with the actual political situation in Ukraine. The multitude of approaches to the study of the formation of political identity is complemented by the consideration of various models of its construction. Fragmental, elite and organic models are considered. Particular attention is paid to the leading role of the state in the process of forming political identity, where the key participants are political elites, the media and civil society. To determine how the perception of the degree of influence of each participant affects the process of political identity formation by the population of Ukraine at different periods of time, with its intermittent outbursts of social activity, the method of factor analysis is used. On the basis of the results of the analysis of the constructed triangular diagrams, two patterns are extracted. According to one, an increase in positive perception and integration into the process of socialization of models of the political identity formation proposed by the political elite is observed in society after each surge in mass protests that leads to a regime change. The other pattern is manifested in the revealed tendentiousness of the influence of the media and political elites on the security level of Ukrainian statehood and the growth of tension in society.

W artykule autorzy analizują kształtowanie się tożsamości politycznej obywateli Ukrainy będącej czynnikiem bezpieczeństwa państwowości ukraińskiej. Podkreślono, że oprócz tożsamości politycznej istnieje wiele innych tożsamości przedstawionych tutaj w postaci matrycy, której składniki nieustannie oddziałują ze sobą, uzupełniają się i wpływają na siebie nawzajem. W ujęciu metodologicznym proces kształtowania się tożsamości politycznej rozpatruje się z punktu widzenia interakcjonizmu symbolicznego, w którym nacisk kładzie się na interakcję polityczną. Dodatkowo, aby obiektywnie ocenić skuteczność kształtowania się tożsamości politycznej i potencjalne negatywne konsekwencje w postaci kryzysu państwowości, mechanizm przekształcania tożsamości sytuacyjnej w podstawową tożsamość polityczną rozpatrywany jest z punktu widzenia poststrukturalizmu. Opracowanie identyfikuje i formułuje kryteria konstruowania tego podstawowego typu tożsamości politycznej, przesłanki ich kształtowania i korelacje z aktualną sytuacją polityczną na Ukrainie. Uzupełnieniem wielości podejść do badań kształtowania się tożsamości politycznej jest uwzględnienie różnych modeli jej konstrukcji. Pod uwagę brane są modele fragmentaryczne, elitarne i organiczne. Szczególną uwagę zwraca się na wiodącą rolę państwa w procesie kształtowania tożsamości politycznej, którego kluczowymi uczestnikami są elity polityczne, media i społeczeństwo obywatelskie. Aby określić, w jaki sposób postrzeganie stopnia wpływu każdego uczestnika przekłada się na proces kształtowania się tożsamości politycznej przez mieszkańców Ukrainy w różnych okresach, z jej okresowymi wybuchami aktywności społecznej, posłużono się metodą analizy czynnikowej. Na podstawie wyników analizy stworzonych w pracy diagramów trójkątnych wyodrębniono dwa wzory. Według jednego z nich, po każdym nasileniu masowych protestów prowadzących do zmiany reżimu obserwuje się w społeczeństwie wzrost pozytywnego postrzegania i nasilenie procesu socjalizacji modeli formowania się tożsamości politycznej proponowanych przez elity polityczne. Drugi wzorzec przejawia się w stwierdzonej tendencyjności wpływu mediów i elit politycznych na poziom bezpieczeństwa ukraińskiej państwowości oraz narastaniu napięcia w społeczeństwie.
Tożsamość polityczna jako czynnik bezpieczeństwa państwowości ukraińskiej
Keywords: political identity; crisis of statehood; security; civil society; universalism; tożsamość polityczna; kryzys państwowości; bezpieczeństwo; społeczeństwo obywatelskie; uniwersalizm